Effect of Progressive Vehicle Tax on Receipt of Motorized Vehicle Transfer Fees - Satriani. M; Masrullah Masrullah (Jurnal Riset Perpajakan: Amnesty, 2022)
This study aims to determine the Effect of Progressive Tax on Motor Vehicles on Receipts of Transfer of Ownership Fees for Motorized Vehicles. The location of this research was conducted in Barru Regency, South Sulawesi Province. The method used in this research is quantitative research using secondary data and hypothesis testing is done using simple linear regression analysis. The statistical test analysis used is the t test to provide how much influence the independent variable has on the dependent variable. The result of this study is that progressive tax has no effect on the receipt of transfer fees for motorized vehicles because due to the rise and fall of progressive tax revenues in 2018 to 2019, a progressive tax rate has been applied with the amount of transfer fees on motor vehicles decreasing.